Determinisme Teologi Islam dalam Pola Gerak Sejarah Indonesia - Nasir, Muhammad (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
This article discusses the determinism of Islamic theology in shaping the laws and movement patterns of Indonesian history. The aim is to explore how religions in Indonesia play a central role in shaping individual and group actions, as well as determining the movement patterns of modern Indonesian history. This discussion uses the speculative historical philosophy concept of historical determinism. In conclusion, the Indonesia historical driving force or it historical pattern are influenced by the theological ideas of religions in Indonesia, including Islam. This is reflected in the formulation of periodization of Indonesian history which is based on the periodization of Indonesian history, which is built on the basis of power entities characterized by religion and the identity of its rulers which is related to a particular religion. Apart from that, its influence can also be read in the style of historiography that developed in Indonesia which is related to religious affairs.